1988
DOI: 10.1007/bf00916554
|View full text |Cite
|
Sign up to set email alerts
|

Selective loss of CD4+ CD45R+ T cells in peripheral blood of multiple myeloma patients

Abstract: The phenotypic distribution of T-lymphocyte subsets in peripheral blood from multiple myeloma (MM) patients shows a reduced proportion of CD4+ cells and a normal proportion of CD8+ cells. The decrease in CD4+ cells could be due to a random process, with all types of CD4+ cells being equally affected, or it could reflect a nonrandom process with selected subsets preferentially reduced. In order to distinguish between these possibilities, double immunofluorescence analysis was performed on blood samples from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…These findings are consistent with previous reports by us [231 and others [14,221, with the exception that greater increases in 6C10h' cells in older Balb/c mice were noted in one study [14]. In the human system, numbers of CD45RBl" and CD2gh' T cells are elevated in elderly individuals [21,24,47]. In both species, these alterations in the phenotypic makeup of the CD4' cell pool appear to occur gradually with age [21][22][23][24]471.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These findings are consistent with previous reports by us [231 and others [14,221, with the exception that greater increases in 6C10h' cells in older Balb/c mice were noted in one study [14]. In the human system, numbers of CD45RBl" and CD2gh' T cells are elevated in elderly individuals [21,24,47]. In both species, these alterations in the phenotypic makeup of the CD4' cell pool appear to occur gradually with age [21][22][23][24]471.…”
Section: Discussionsupporting
confidence: 95%
“…CD4' cells were cultured in the presence of accessory cells derived from young mice, and were stimulated with 2C11 s or 2C11 i. At 24,48, and 72 h of culture, cells were assayed for I3HITdR uptake and supernatants were assayed for IL-2 (CTLL.6 assay) and (1 1.6 assay) content. The data represent the peak response for each group.…”
Section: Cytokine Production By Cd4' Cells From Old Micementioning
confidence: 99%
“…3 The depression of the CD4/8 ratio is usually more obvious in patients with progressive disease. [4][5][6] It has been reported that within the CD4 þ T cell compartment, there is a selective loss of cells in the naive CD4 þ CD45R þ subset, 7,8 suggesting an enrichment of memory CD4 þ cells and a failure in the differentiation pathway to give rise to new naive CD4 þ T cells. 8 Conversely, in patients with myeloma at diagnosis, a reduction in total and activated CD4 þ T cells but not naive CD4 subsets has also been reported.…”
Section: Cd4 and Cd8 T Cells In Myelomamentioning
confidence: 99%
“…Samples were collected at all stages of the disease patients with myeloma can have an altered CD4:CD8 ratio including presentation (n = 35), plateau/stable phase (n = 39) which is related to a decrease in naive CD4 cells in advanced and progressive disease (n = 45). Patients were treated accordstages of the disease, 11,12 an increased number of large granuing to the ALSG myeloma trial protocol which involved multilar lymphocytes and activated T cells 10,13,14 and a sensitivity agent therapy (prednisone, cyclophosphamide, doxorubicin and bis-chloronitrosourea) plus or minus alpha-interferon. 29 Patients over 70 years were treated with melphalan and receptor ␤ probe used was a 0.4 kb fragment derived from a cDNA which includes the T cell receptor CT␤2 region of light chain disease (one and one ) were used to purify IgG and light chains, respectively.…”
mentioning
confidence: 99%